Dynamic near-infrared spectroscopy assessment as an important tool to explore pulmonary arterial hypertension pathophysiology. Issue 1 (5th January 2017) - Panagiotou, Marios; Vogiatzis, Ioannis; Louvaris, Zafeiris; Jayasekera, Geeshath; McKenzie, Alison; Mcglinchey, Neil; Baker, Julien S.; Church, Alistair C.; Peacock, Andrew J.; Johnson, Martin K.
We thank S. Dimopoulos and co-workers for their particular interest in our study [1] and their contributions to this issue. The peripheral muscle hypothesis in pulmonary arterial hypertension (PAH) [2] is certainly of great and growing interest due to the potential of muscle function as a target for meaningful intervention. Accordingly, our study explored the value of quadriceps muscle oxygenation profiles in patients with PAH by means of near-infrared spectroscopy (NIRS) [1]. The satisfactory correlation between vastus lateralis muscle tissue oxygenation index ( S tO2 ) and mixed venous oxygen saturation ( S vO2 ) both at rest and during exercise support the use of NIRS in the noninvasive investigation of patients with PAH. Importantly, they suggest that skeletal muscle oxygenation profiles reflect the pathophysiology of PAH. Near-infrared spectroscopy offers a qualitative, noninvasive indication of mixed venous oxygen saturation in PAH http://ow.ly/MctV306eEYC